The experience of bilateral cochlear implantation in a child with LEOPARD syndrome. (November 2016) - Vermeire, Katrien; Wexler, Leslie; Vambutas, Andrea
Abstract: We present a 3-year old boy with Leopard syndrome. His clinical manifestations included a congenital bilateral sensorineural hearing loss. He underwent cochlear implantation on the right side at age 1 year and on the left side at age 1.5 years. The patient is doing very well and mainstreamed in a regular pre-school program with a teacher of the deaf and home based speech therapy. Bilateral cochlear implantation in the case of a child with Leopard syndrome can be successful.